2016
DOI: 10.1155/2016/5230642
|View full text |Cite|
|
Sign up to set email alerts
|

High Expression of PTGR1 Promotes NSCLC Cell Growth via Positive Regulation of Cyclin-Dependent Protein Kinase Complex

Abstract: Lung cancer has been the most common cancer and the main cause of cancer-related deaths worldwide for several decades. PTGR1 (prostaglandin reductase 1), as a bifunctional enzyme, has been involved in the occurrence and progression of cancer. However, its impact on human lung cancer is rarely reported. In this study, we found that PTGR1 was overexpressed in lung cancer based on the analyses of Oncomine. Moreover, lentivirus-mediated shRNA knockdown of PTGR1 reduced cell viability in human lung carcinoma cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…Moreover, phosphorylation-dependent activity was also found between the proteins in the complex [ 46 – 50 ]. This complex plays an important role in cell cycle control, whereas its deregulation could accelerate tumor growth [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, phosphorylation-dependent activity was also found between the proteins in the complex [ 46 – 50 ]. This complex plays an important role in cell cycle control, whereas its deregulation could accelerate tumor growth [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, GCLC plays a crucial role in drug resistance and is considered to be a potential drug target in lung and other cancers [ 40 - 42 ]. Interestingly, another known NRF2-regulated gene, PTGR1 (prostaglandin reductase 1), is highly expressed in NSCLC, promotes cancer cell growth through positive regulation of the cyclin-dependent protein kinase complex, and is considered to be a druggable target in lung and hepatocellular carcinoma [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since cell proliferation is closely related to the cell cycle, we further analyzed cell cycle distribution and found that aspirin significantly increased the cell population in the G0/G1 phase. Cell cycle regulatory proteins play a crucial role in the regulation of the cell cycle [ 37 ]. In tumor cells, the levels of p21 are usually low, which permits unchallenged proliferation.…”
Section: Discussionmentioning
confidence: 99%